2021
DOI: 10.3390/life11060577
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Decreases Negative Affect by Modulating Orbitofrontal-Amygdala Connectivity in Adolescents

Abstract: Long-term negative affect in adolescence is associated with impairment in quality of life, interpersonal function, and social adaptation. Although physical exercise could decrease negative emotion, the underlying mechanism remains largely unknown. Acute exercise with controlled intensity might be a good experimental paradigm to unravel the potential neural mechanisms underlying the effects of physical exercise on negative affect. In this study, twenty-three males in late adolescence were randomly assigned to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
(55 reference statements)
0
7
1
1
Order By: Relevance
“…Less is known about how exercise affects the amygdala. To date, most research has focused on the effect of exercise on emotion regulation, showing that exercise can boost prefrontal function (Ligeza et al, 2021) and can increase connectivity between the prefrontal cortex and amygdala in ways that have been interpreted as indicative of improved emotion regulation (Ge et al, 2021). If exercise is indeed increasing hippocampal function while decreasing amygdala engagement, it may create an intriguing scenario in which an emotional experience is remembered primarily with hippocampal-binding mechanisms engaged.…”
Section: Aerobic Exercisementioning
confidence: 99%
“…Less is known about how exercise affects the amygdala. To date, most research has focused on the effect of exercise on emotion regulation, showing that exercise can boost prefrontal function (Ligeza et al, 2021) and can increase connectivity between the prefrontal cortex and amygdala in ways that have been interpreted as indicative of improved emotion regulation (Ge et al, 2021). If exercise is indeed increasing hippocampal function while decreasing amygdala engagement, it may create an intriguing scenario in which an emotional experience is remembered primarily with hippocampal-binding mechanisms engaged.…”
Section: Aerobic Exercisementioning
confidence: 99%
“…Physical activity could stimulate the release of neurotransmitters such as dopamine and (-)-noradrenaline, increase the functional connection between the amygdala and the orbitofrontal cortex, and enhance the execution function, thus reducing anxiety and depression, as well as increasing euphoria and sense of accomplishment [40][41][42]. The results of the studies included in this review are in line with previous findings [43][44][45] that either regular long-term exercise, short-term exercise or a physical function test exerted varying degrees of positive effects on the psychological responses, such as relieving confusion, depression, and other negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that acute exercise can lead to a change in blood flow, and then affect the working memory of individuals. Some research has suggested that acute exercise-induced lowering of negative affect may be mediated by the bilateral amygdala in relation to the functional connectivity of cognitive control and limbic networks, because exercise groups exhibited increased functional connectivity between the right amygdala and right orbital frontal cortex ( Ge et al 2021 ), suggesting that acute exercise can effectively improve individual cognition. The influence of music listening on cognition can be explained as follows.…”
Section: Discussionmentioning
confidence: 99%